PENINGKATAN KETERAMPILAN MENULIS SISWA MELALUI METODE SQ3R PADA PEMBELAJARAN TEMATIK KELAS V SD SAMPANGAN - Atmajati, Annisa; Aliim Hidayat, Rosidah; Widi Astuti, Yanuarita (Universitas Sarjanawiyata Tamansiswa, 2022)
The purpose of this study was to determine the improvement of writing skills by using learning methods SQ3R. The action hypothesis is a learning method SQ3R can improve the skills of writing interview reports. This type of research is classroom action research. The technique of collecting data uses observation, tests, documentation. The instruments of this study were observation sheets and writing tests. The data analysis technique is descriptive qualitative and quantitative. The results showed that the use of SQ3R learning methods could improve writing skills. The increase can be seen from the average percentage of 50.83% in pre-cycle in the sufficient category, increasing in the first cycle to 68,02% in the good category, and increasing in the second cycle to 80.31% in the very good category. The above results are strengthened by the results of observations of learning activities. The average percentage on prasiklus is 53,58% in the sufficient category, increasing in the first cycle to 69,27% in the good category, and increasing again in the second cycle to 83,33% in the very good category.